Urgensi Qawaid Fiqh Dalam Istinbath Hukum Ekonomi Syariah Kontemporer (Gunung Djati Conference Series, 2025)
Qawaid Fiqh is a basic rule in Islamic jurisprudence that plays an important role in theistinbath of contemporary Islamic economic law. This study uses a qualitative method toanalyze its urgency in dealing with modern economic issues. The results show that QawaidFiqh facilitates the determination of law in new cases that are not directly regulated byIslamic texts, maintains legal consistency, and ensures alignment with Islamic maqasid. Itsapplication in Islamic transactions such as murabahah and salam contracts proves itseffectiveness in creating transparent and fair legal decisions. The main challenges includevariations in interpretation, limited human resources, and the influence of globalization andtechnological innovation. This study emphasizes the need for collaboration between variousparties to strengthen the application of Qawaid Fiqh in a dynamic and sustainable Islamiceconomic system.